Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/bja/aew309
|View full text |Cite
|
Sign up to set email alerts
|

MitoVitE, a mitochondria-targeted antioxidant, limits paclitaxel-induced oxidative stress and mitochondrial damage in vitro, and paclitaxel-induced mechanical hypersensitivity in a rat pain model

Abstract: Paclitaxel affected mitochondrial function and glutathione in DRG cells, which was abrogated by MitoVitE but not Trolox, without decreasing cancer cell cytotoxicity. In rats, paclitaxel-induced mechanical hypersensitivity was ameliorated by MitoVitE treatment to an extent similar to duloxetine. These data confirm mitochondria as a mechanistic target for paclitaxel-induced damage and suggest mitochondria targeted antioxidants as future therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 38 publications
(35 reference statements)
4
46
0
1
Order By: Relevance
“…Astaxanthin and vitamin E have shown antioxidant effects in cardiac tissues and exerted beneficial effects on mitochondrial homeostasis ; however, the antioxidant effects of β‐cryptoxanthin have never been investigated. The present study found that these antioxidants decreased plasma and cardiac TBARS levels in treated mice compared to control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin and vitamin E have shown antioxidant effects in cardiac tissues and exerted beneficial effects on mitochondrial homeostasis ; however, the antioxidant effects of β‐cryptoxanthin have never been investigated. The present study found that these antioxidants decreased plasma and cardiac TBARS levels in treated mice compared to control mice.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Mitochondria-targeted antioxidants, such as mitoVitE and melatonin, also attenuated paclitaxel-induced neuropathic pain. 67,68 However, despite positive results from preclinical studies, results from clinical studies are less satisfying. Clinical trials using nutraceuticals with antioxidant properties, including vitamin E, acetyl-L-carnitine, glutamine, glutathione, vitamin B6, omega-3 fatty acids, and a-lipoic acid, have reported controversial results.…”
Section: Contribution Of Nitro-oxidative Stress To Cipnmentioning
confidence: 99%
“…Preclinical data have demonstrated great promise for compounds targeting this pathway, such as pifithrin-l, HDAC6 inhibitors, and metformin, as well as antioxidants and peroxynitrite decomposition catalysts as prophylactic treatment of CIPN. 24,27,30,47,[61][62][63][64][65][66][67][68]110 It is interesting to note that HDAC6 inhibitors were found to be effective in both preventing and reversing CIPN, 30 with reported synergistic effects on tumor killing in combination with chemotherapy. 41,42 Given these unique features, HDAC6 inhibition may be a preferred treatment option for patients already receiving chemotherapy.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ці процеси відбуваються на тлі оки-слювальних ушкоджень, тісно пов'язаних із мітохо-ндріальною дисфункцією клітин [14,7,12,6]. Зроб-лено висновок про можливий напрямок лікування чи корекції таких станів антиоксидантами, але на доказ цього проведена обмежена кількість дослі-джень із вивченням нейропротекторної дії антиок-сидантів [2,13,11].…”
Section: ультраструктурні зміни в сітківці ока при корекції паклітаксunclassified